Find the sum of all between and inclusive for which
Details and Assumptions
It is given that .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rewrite the equation as:
1 − tan 2 θ 2 tan θ = 3 tan θ
Note that the left side is undefined for θ = 4 5 ∘ , 1 3 5 ∘ , 2 2 5 ∘ , 3 1 5 ∘ while the right side is undefined for θ = 9 0 ∘ , 2 7 0 ∘ . In particular, we can thus multiply both sides of the equation by 1 − tan 2 θ , since for all such other values of 0 ∘ ≤ θ ≤ 3 6 0 ∘ , 1 − tan 2 θ = 0 . We then have:
2 tan θ = 3 tan θ ( 1 − tan 2 θ ) ⇒ tan θ ( 3 tan 2 θ − 1 ) = 0
For tan θ = 0 , we have θ = 0 ∘ , 1 8 0 ∘ , 3 6 0 ∘
For tan θ = 3 1 , we have θ = 3 0 ∘ , 2 1 0 ∘
For tan θ = − 3 1 , we have θ = 1 5 0 ∘ , 3 3 0 ∘
The sum of all these values is then thus 1 2 6 0 ∘